(untitled) (Mugda Medical College Journal, 2025)
Anaplastic large cell lymphoma (ALCL) is rare. Approximately 2% of adult non-Hodgkin lymphoma diagnoses are ALCL. Most people are diagnosed when the cancer is more advanced. In advanced stages, the cancer may have spread to organs, like lungs, liver and bone. Patients experience symptoms based on which body parts are affected, e.g., pressure in the chest and a frequent cough may signify the presence of the ALCL affected the lungs. Here, we present an incidental finding of anaplastic large cell lymphoma (ALCL) in a 16-year-old boy with multiple painful soft tissue swellings. The case is presented out of an academic interest and to recognize its rarity in clinical practice. Most children and adolescents with ALCL have presenting symptoms of advanced stage disease (70% present with stage III–IV disease). Peripheral or abdominal lymphadenopathy, extranodal infiltrates, bone marrow involvement, systemic symptoms (especially high fever, weight loss). One-third of the affected children usually relapse and one-half of them ultimately die. Essential features include: T-cell lymphoma, characteristic hallmark cells, CD30 diffusely and strongly positive, ALK positive, and ALK gene rearrangement. Among the treatment modalities, the first line of treatment includes chemotherapy with APO regimen in accordance with ALCL 99, or NHL-BFM 90 protocol. In relapsed or refractory cases, combination or single agent chemotherapy are effective. High dose chemotherapy followed by stem cell transplant are also in practice. Another available treatment is targeted therapy with brentuximab vedotin (anti-CD30), or ALK inhibitors (e.g., crizotinib). In immunotherapy, checkpoint inhibitors (e.g., nivolumab) are under trial. Last but not the least, radiotherapy can be applied on the affected sites. Mugda Med Coll J. 2025; 8(2): 167-170